(untitled) (European journal of volunteering and community-based projects, 2024)
Starting from 2021 the strategic planning process in the Italian public sector benefited from the new Integrated Activity and Organization Plan (PIAO). Such a tool has been introduced with the aim of harmonizing and simplifying the three-year planning process through the integration of the different perspectives involved in the value generation and measurement. Furthermore, according to this new approach, the generative path of public value has been rethought and innovated in terms of multidimensional well-being with emphasis to the non-financial perspective. With this regard, the set of Sustainable Development Goals (SDGs) represents a useful key to understand the consistency of both the strategies and the impacts of performance. Among the public-sector organizations that mostly influence the achievement of the SDGs, universities play a very important role. Therefore, the aim of this work is to identify an approach to detect the level of materiality with respect to the 17 SDGs within the PIAOs of Italian universities. The proposed interpretative model has been tested by examining 48 three-years PIAOs relating to the period 2023-2025. The study uses the content analysis methodology to investigate which of the 17 SDGs the Italian public universities’ PIAOs are based on. 48 documents have been extracted from the official ministerial platform. The PIAOs examined show a limited propensity to integrate the SDGs within the strategic process. The inclusion of the 17 SDGs in the programmatic lines of universities, when it occurs, does not present homogeneous characteristics. However, the SDGs that are disclosed with a percentage greater than 80% are associated in a consistent manner with respect to the mission to which they are aligned. This study designs a first approach that can be adopted to account for the SDGs materiality in the strategic planning process in the higher education. This analysis also tests the recommended methodology to investigate a sample of 48 PIAOs from Italian public universities.